THE STRATEGY DEVELOPMENT OF TOURISM BAHARI IN THE PESONA BEACH, KECAMATAN RUPAT UTARA, KABUPATEN BENGKALIS, PROVINSI RIAU - Rio Jenero Aritonang; Hamdi Hamid; Firman Nugroho (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was pointed to identify tourism’s condition, to study of strategy development and to find the alternative strategy development bahari tourism in Pesona Beach, Kecamatan Rupata Utara, Kabupaten Bengkalis, Provinsi Riau. The method of this research is study of case. The result showed that Pesona Beach have a tourism potention with long white sand in the beach, extending along ±17 km from Teluk Rhu to Tanjung Punak. Beside that, it has history destination as Puteri Sembilan and Puteri Tujuh Grave and estates from 100 years ago. The people of rupat utara have tradition “Mandi Safar”. Local Government as part of stakeholder built some infrastructure for supporting income from Development of Bahari Area in Pesona Beach such as Homestay, harbour,offices of local UPTD and connection between desa to kecamatan which is being built. From the result of the urgency analysis (SWOT analysis), showed the priority of development strategy; first step is getting the 2.4 point to do development of culture and bahari tourism (ecotourism); second step is getting 2.12 point to accelerate development of land access infrasctructure between kecamatan; and the third step is getting 1.97 point to prosper the local especially for who stay there.